Optimalisasi Fase Dan Durasi Lampu Lalu Lintas Bundaran Digulis Pontianak - Sijabat, Harry Evendy; Nilamsari Kusumastuti; Fransiskus Fran (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Digulis Roundabout Pontianak is one of the intersections that has a fairly heavy traffic flow that often causes congestion at this intersection. Therefore, it is necessary to optimise the phase and duration of traffic lights by applying fuzzy graph   to reduce congestion at thy are. In this study, traffic flows are represented as vertices and flows that cross or intersect are represented as edges, then the degree of membership of the vertices is represented as the density of the traffic flow and the degree of membership of the edges is represented as the level of conflict between two vehicle flows that can cause traffic conflicts. Based on this representation, a fuzzy graph  consisting of 14 vertices and 42 edges is obtained. Furthermore, fuzzy graph formation is modelled as a fuzzy graph colouring problem. Fuzzy graph colouring using the concept of Eslachi and Onagh (2006) produces chromatic numbers for  ∝, namely  ,  ,and   and the largest chromatic number is 4, meaning that there are 4 traffic phases obtained at Digulis Roundabout Pontianak. Next the optimal duration of each phase was found using the Webster method. The green light duration for each phase of Digulis Roundabout Pontianak is obtained, namely, Jenderal A Yani 2 street for 53 seconds, Jenderal A Yani 1 street for 46 seconds, Daya Nasional street for 15 seconds, Prof. Hadari Nawawi street for 18 seconds Keywords : traffic jam, fuzzy graph , fuzzy graph colouring, Webster method